Water Extract of Senecio scandens Buch.-Ham Ameliorates Pruritus by Inhibiting MrgprB2 Receptor - Ye F; Jiang Y; Zhang J; Zong Y; Yu M; Chen C; Zhu C; Yang Y; Jia K; Chen G; Tang Z (Dove Medical Press, 2022)
Fan Ye,1,* Yucui Jiang,1,2,* Jian Zhang,1 Yingxin Zong,1 Mei Yu,1,3 Cuihua Chen,2 Chan Zhu,1 Yan Yang,1 Keke Jia,1 Gongxi Chen,4 Zongxiang Tang1 1School of Medicine & Holistic Integrative Medicine, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China; 2School of Chinese Medicine & School of Integrated Chinese and Western Medicine, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China; 3Department of Pharmacy, Taizhou Hospital of Traditional Chinese Medicine, Nanjing University of Chinese Medicine, Taizhou, People's Republic of China; 4School of Pharmaceutical Sciences, Jishou University, Jishou, People's Republic of China*These authors contributed equally to this workCorrespondence: Gongxi Chen; Zongxiang Tang, Email chengongxi2011@163.com; zongxiangtang@njucm.edu.cnBackground: Senecio scandens Buch.-Ham (S. scandens) belongs to the Compositae family. As a Traditional Chinese medicine, S. scandens has been used in China to treat conjunctivitis, mastitis and vaginitis, it also has the function of antibacterial and relieving itching.Methods: Water extract of S. scandens (WSS) was prepared and its quality was controlled by HPLC. The antipruritic effects of WSS were evaluated by itch behavioral experiments. The oxazolone and compound 48/80 were induced to mice scratch behavior, scratch was recorded 30 min after sensitization. The relationship between the antipruritic mechanism and MrgprB2 on mast cell was studied by using mast cell-deficient Kit (W-sh) "Sash" mice and MrgprB2−/− mice. The mast cells were observed by toluidine blue staining. In vitro, the effects of WSS on MrgprB2 were studied by calcium imaging; The whole-cell patch clamp method recorded the MrgprB2 mediate voltage-dependent currents in mast cells.Results: The content of rutin (0.012%) and hyperin (0.014%) in the WSS were determined. WSS could ameliorate the pruritus induced by Oxazolone (inhibition was 41.19%, p = 0.004) and compound 48/80 (inhibition was 50.29%, p = 0.001). Meanwhile, WSS could reduce the number of mast cells in mice skin tissue with allergic contact dermatitis (ACD) (p = 0.002) or compound 48/80 (p = 0.013). In addition, WSS could inhibit the calcium influx (1 mg/mL: p = 0.001, 3 mg/mL: p < 0.0001) and the voltage-dependent currents induced by activation of MrgprB2 on mast cell. WSS also attenuated the calcium influx induced by compound 48/80 in HEK293 cells overexpressing MrgprB2/X2.Conclusion: These results showed that WSS could ameliorate pruritus by inhibiting MrgprB2 receptor on mast cells.Graphical Abstract: Keywords: Senecio scandens Buch.-Ham, pruritus, mast cell, MrgprB2 receptor